Unmet Medical Needs in the Management of Ulcerative Colitis: Results of an Italian Delphi Consensus. (2nd September 2019) - Daperno, Marco; Armuzzi, Alessandro; Danese, Silvio; Fries, Walter; Liguori, Giuseppina; Orlando, Ambrogio; Papi, Claudio; Principi, Mariabeatrice; Rizzello, Fernando; Viscido, Angelo; Gionchetti, Paolo
Abstract : Background. The lifelong and remitting nature of ulcerative colitis results in considerable disability and a substantial negative impact on quality of life. The major goal of the therapy of ulcerative colitis is considered to be the modification of the course of the disease, so that the patient's quality of life can be improved while minimising disease-related disability. Although considerable progress in understanding the molecular pathways involved in ulcerative colitis has led to improved treatment options, there is currently no definitive cure for ulcerative colitis, there remain considerable unmet needs in terms of long-term efficacy and safety, and there are many patients who continue to be burdened by physical and psychological symptoms. Defining unmet needs can help to increase the awareness of the shortcomings of current therapeutic management and highlight the need to achieve not only a control of clinical symptoms but also control of mucosal healing, in order to attain the best possible long-term outcomes. Methods. With the aim of providing a better understanding of the unmet needs of patients towards improving overall care, a Delphi process was used to obtain consensus among a group of Italian ulcerative colitis experts. The consensus group met with a major focus of delineating the unmet needs of current treatment strategies and overall management of ulcerative colitis, while also focusing on quality of life and patient care. Results. Three main areas were identified: (i) treatment, (ii) monitoring and risk management, and (iii) patient-related issues. A high level of consensus was reached on all but one of the statements identified. Conclusions. The findings arising from the Delphi process provide valuable insights into the unmet needs in the management of moderate-to-severe ulcerative colitis from the clinician's perspective, while emphasising the benefits of therapeutic individualization and suggesting areas that need additional study with the aim of optimising the treatment of patients with ulcerative colitis.